Measuring Financial Capability : A New Instrument and Results from Low- and Middle-Income Countries - Kempson, Elaine; Perotti, Valeria; Scott, Kinnon (World Bank, Washington, DC, 2013)
In 2008 the Ministry of Finance of the Russian Federation established a Trust Fund to be administered by the World Bank with the goal of advancing financial capability in low-and middle-income countries. This report documents the multiyear effort to develop measures of financial capability and summarizes the findings of this project. The generous funding of the Russia Trust Fund (RTF) allowed for the application of a very rigorous research-based process of defining the concept of financial capability and developing data collection survey methods and analytical procedures to measure the level and distribution of financial capability within low- and middle-income countries. This involved the active participation of World Bank staff, expert consultants, country-based teams, government officials, and researchers from 12 middle and low-income countries. Financial capability, the capacity to manage financial resources and use financial services in a way that best suits individual needs and the prevalent social and economic conditions, can contribute significantly to both the level and efficacy of financial inclusion. The multistep process used to develop tools to measure financial capability in low and middle-income countries entailed: 1) development of an operational definition of financial capability through identification of its key manifestations; 2) development and cognitive testing of survey questions to measure the manifestations; 3) data collection; 4) identification of the key components and domains of financial capability; and 5) identification of potential target groups for policy interventions. The goal of the World Bank's RTF financial capability survey is to capture information on the manifestations of financial capability through individuals' behavior, skills, and attitudes related to managing the finances for which they are responsible. Because it focuses on behaviors and actions, the survey instrument cannot be used to assess the financial capability of people who neither manage their own finances nor participate in household financial decisions. Finally, populations of individual countries can be segmented into groups with varying levels of capability across all components. The strengths and weaknesses of these groups can be determined-as can their characteristics. These groups can be as fine-tuned as is required to inform approaches to increasing levels of financial capability.